The Use of English Short Animation Movies to Improve Students’ Listening Skill: A Study at The First Grade of SMPN 1 Lingsar Academic Year 2022/2023 - Putri Yunita; Arafiq Arafiq; Atri Dewi Azis; Sahuddin Sahuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research aims to find out the effectiveness of using English Short Animation Movies to improve students listening skills at SMPN 1 Lingsar academic year 2022/2023. This research uses quantitative method with an experimental design. The design of the research is quasi experimental research with nont-equivalent control group design two group Experimental group and control group. The population and sample of this research are all first-grade students at SMPN 1 Lingsar.The sample was selected based cluster random sampling technique. The data analysed by using Microsoft Excel and the SPSS program. After analyzing the data, the results were compared between t-test and t-table value of the Experimental and Control groups.,in the experimental group the t-test value is 5.562. The table above shows that t-test value in the experimental group (5.562) is higher than the t-value table (1.67) for alpha 0.05 and (2.66) for alpha 0.01 which means that the result of the experimental t-test are significant. Meanwhile, the results of the t-test from the control group (2.057) in the table above shows that t-test value in the control group ( 2.057) is lower than the t-table value (1.67) alpha 0.05 and (2.66) for alpha 0.01 which means that the results of the t-test control group are not significant. This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So it can be concluded that there is a significant effect in the use of English short animation movie to improve students listening skills at the first grade of SMPN 1 Lingsar.